CooperAR: supporting the design and implementation of augmented inclusive educational scenarios - Quintero, Jairo; Baldiris, Silvia; Cerón, Jhoni (Frontiers in Education, 2025)
There are sufficiently studied advantages of Augmented Reality (AR) in education. However, studies regarding the impact of AR in educational inclusion are still scarce; particularly, no methodologies that help educational institutions, particularly teachers, in addressing diversity in the classroom using AR are reported. This study describes and evaluates CooperAR, a methodology for co-creating augmented and inclusive educational scenarios, considering three conceptual principles: cooperative learning (CL), universal design for learning (UDL) and co-creation between students and teachers. CooperAR was evaluated under three dimensions, inclusion, cooperation and quality. A quasi-experimental design with a descriptive scope carried out in an educational institution in the South of Colombia, with 63 students pre-organized into two groups. Results demonstrated that CooperAR favors the co-creation of augmented and inclusive educational scenarios among heterogeneous groups, provoking the participation of all students, and evidencing that cooperation is a catalyst for inclusive learning. The evaluation confirms that CooperAR is an effective and innovative methodology that enhances educational inclusion through Augmented Reality. Promoting its adoption in educational settings could help institutions better address the needs of all students, particularly those at risk of exclusion.